Perceptions and attitudes towards fact-checking in Greece: Α quantitative audience research: A quantitative audience research - Poulakidakos, Stamatis; Demertzis, Nicolas; Linardis, Apostolos (Επιστήμη και Κοινωνία: Επιθεώρηση Πολιτικής και Ηθικής Θεωρίας, 2024)
This article studies the Greek public’s perceptions and attitudes towards fact-checking. We conducted quantitative audience research with a nationwide convenience sample of 1370 people (aged 17+) using an online questionnaire during the period 26/11/2021 to 26/05/2022. As evident from our own research, parts of the (digital) audience seem to ‘respond’ in a positive way to fact-checking organizations. In terms of the most important findings, political inte rest has the highest effect on the dependent variables of our research questions. More specifically, it has the relative higher positive and statistically significant effect on three dependent variables (‘awareness of fact-checking organizations’, ‘ability to spot fake news on the internet’ and ‘investigation of the accuracy of a strange news item’). Self-positioning on the left-right axis has the relative highest positive effect on two dependent variables (‘belief that the pandemic is an overreaction’ and ‘effectiveness of fact-checking organizations’).